Defining the Ideal "Nail Exit Path" of a Tibial Intramedullary Nail—A Computed Tomography Analysis of 860 Tibiae. Issue 11 (November 2021) - Trompeter, Alex; Williamson, Mike; Bates, Peter; Petersik, Andreas; Kelly, Michael
Abstract : Objectives: To identify the ideal distal nail position in the distal tibia, using a computed tomography analysis. Methods: Three-dimensional models of 860 left tibiae were analyzed using the Stryker Orthopaedic Modeling and Analytics software (SOMA, Stryker, Kiel, Germany). The nail axis was defined by 7 center points at the middle of the inner cortical boundary. The point where this line fell relative to the center of the tibial plafond in both the anteroposterior and mediolateral planes was calculated. Results: The mean mediolateral offset of the tibial nail exit path was 4.4 ± 0.2 mm (95% confidence interval) lateral to the center of the tibial plafond. The mean anteroposterior offset of the tibial nail exit path was 0.6 ± 0.1 mm anterior to the center of the tibial plafond. Conclusions: We have presented an anatomic study analyzing the ideal nail exit path using computed tomography scans of 860 tibiae. We defined that the ideal nail exit path of a tibial nail is lateral with respect to the center of the tibial plafond. This is supported by previous clinical studies and has significant implications for preventing malalignment when treating distal tibial fractures with intramedullary nailing.